2012
DOI: 10.1152/japplphysiol.00435.2011
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome signature of resistance exercise adaptations: mixed muscle and fiber type specific profiles in young and old adults

Abstract: This investigation examined the effects of acute resistance exercise (RE), progressive resistance training (PRT), and age on the human skeletal muscle Transcriptome. Two cohorts of young and old adults [study A: 24 yr, 84 yr (n = 28); study B: 25 yr, 78 yr (n = 36)] were studied. Vastus lateralis biopsies were obtained pre- and 4 h post-RE in conjunction with the 1st and 36th (last) training session as part of a 12-wk PRT program in study A, whereas biopsies were obtained in the basal untrained state in study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
264
4
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(287 citation statements)
references
References 60 publications
17
264
4
2
Order By: Relevance
“…In previous studies with healthy human subjects, e.g., several genetic variations (Riechman et al 2004;Devaney et al 2009;Walsh et al 2012;Van Deveire et al 2012), differences in skeletal muscle gene Raue et al 2012;Phillips et al 2013) and microRNA expression (Davidsen et al 2011), phosphorylation status of signaling proteins (Mayhew et al 2011;Mitchell et al 2013), androgen receptor concentrations (Ahtiainen et al 2011;Mitchell et al 2013), and satellite cell count (Petrella et al 2008) have been suggested to segregate high and low responders to RTinduced muscle hypertrophy. The physiological aspects of individual variation in phenotype responses to RT are apparently very complex phenomena and more studies specifically focused on high and low responders are required to reveal unambiguously the mechanisms of individual differences in RT-induced adaptations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies with healthy human subjects, e.g., several genetic variations (Riechman et al 2004;Devaney et al 2009;Walsh et al 2012;Van Deveire et al 2012), differences in skeletal muscle gene Raue et al 2012;Phillips et al 2013) and microRNA expression (Davidsen et al 2011), phosphorylation status of signaling proteins (Mayhew et al 2011;Mitchell et al 2013), androgen receptor concentrations (Ahtiainen et al 2011;Mitchell et al 2013), and satellite cell count (Petrella et al 2008) have been suggested to segregate high and low responders to RTinduced muscle hypertrophy. The physiological aspects of individual variation in phenotype responses to RT are apparently very complex phenomena and more studies specifically focused on high and low responders are required to reveal unambiguously the mechanisms of individual differences in RT-induced adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…The robust study of individual responses to unilateral upper arm RT by Hubal et al (2005) showed that of 585 subjects, approximately 6 % showed practically no gains in muscle size. Also, other RT studies have reported that, in some subjects, muscle size gains are either minimal or non-existent following a training period Davidsen et al 2011;Raue et al 2012;Mitchell et al 2013;Phillips et al 2013). Similarly to muscle size responses, gains in muscle strength during RT are also highly individual (Hubal et al 2005;Erskine et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The proposed system is also compared with the system presented in [2] and [19], in which genes are identified for three categories (male young versus male old, female young versus female old and male old versus female old) from total of 54623 genes. In order to have a fair comparison, the same number of genes are selected from MFS and compared with the genes identified in [2] and [19].The evaluation metrics used in this study are: Classification accuracy, Sensitivity and Specificity.…”
Section: Resultsmentioning
confidence: 99%
“…Datasetsare publicly available in the Gene Expression Omnibus (GEO) database [2], [19]. A total of 58 individuals were involved in this investigation:…”
Section: A Micro Array Gene Expression Data Setmentioning
confidence: 99%
See 1 more Smart Citation